Significant Analysis of Heart Disease Detection Using Artificial Intelligence Algorithms - Varsha, Varsha; Maran, P. Sardar (Journal of Neonatal Surgery, 2025)
Lifestyle changes affect human health significantly, leading to heart disease and Sudden death in patients. The Healthcare Industry faces multiple challenges in managing and treating the increasing number of patients according to their disease severity level. The challenges for medical experts include early identification of symptoms & timely treatment to save them. The non-availability of efficient, effective, and automatic screening methods and limited medical data analytics augment these challenges. Some current medical applications have stated that Artificial intelligence algorithms provide efficient outcomes in predicting heart diseases. This paper conducted a detailed survey on various artificial intelligence algorithms used for heart disease prediction from various related datasets. The survey aims to identify the limitations and factual problem statements and identify solutions.